Experimental results of the simultaneous measurement of spatially varying phase and polarization. - Rothau, Sergej; Kellermann, Christine; Lindlein, Norbert (116. Annual Meeting of the DGaO, 2015)

Experimental results of the simultaneous measurement of spatially varying phase and polarization - Rothau, Sergej; Kellermann, Christine; Lindlein, Norbert (2015)

Grazing incidence interferometry for rough convex aspherics - Schwider, Johannes; Kellermann, Christine; Lindlein, Norbert; Rothau, Sergej; Mantel, Klaus (arXiv, 2016)

Polarization and phase-shifting interferometry for arbitrary, locally varying polarization states - Rothau, Sergej; Kellermann, Christine; Mayer, Simon; Mantel, Klaus Peter; Lindlein, Norbert (Applied Optics, 2017)
This publication presents what we believe is a novel interferometric method for the simultaneous measurement of the phase and state of polarization of a light wave with arbitrary polarization; in particular, it can be varying elliptical. The measurement strategy is based on variations of the reference wave, concerning phase and polarization and processing the interference patterns so obtained. With this method, which is very similar to classical phase-shifting interferometry, the general analysis of spatially variant states of polarization and their phase fronts can be done in one measurement cycle. Furthermore, the analysis of different optical elements regarding the impact on the polarization and phase of the incoming light can be realized. After the theoretical description of the method and the mathematical discussion of different algorithms, the realized measurement setup is presented. Afterward, the accuracy of the method is discussed.

Simultaneous measurement of phase and local orientation of linearly polarized light: Implementation and measurement results - Rothau, Sergej; Kellermann, Christine; Nercissian, Vanusch; Berger, Andreas; Mantel, Klaus; Lindlein, Norbert; Lindlein, Norbert (Applied Optics, 2014)
Optical components manipulating both polarization and phase of wave fields find many applications in today's optical systems. With modern lithography methods it is possible to fabricate optical elements with nanostructured surfaces from different materials capable of generating spatially varying, locally linearly polarized-light distributions, tailored to the application in question. Since such elements in general also affect the phase of the light field, the characterization of the function of such elements consists in measuring the phase and the polarization of the generated light, preferably at the same time. Here, we will present first results of an interferometric approach for a simultaneous and spatially resolved measurement of both phase and polarization, as long as the local polarization at any point is linear (e.g., for radially or azimuthally polarized light).

Theoretical description of a method for simultaneous measurement of phase and arbitrary polarization - Kellermann, Christine; Rothau, Sergej; Lindlein, Norbert (116. Jahrestagung der DGaO, 2015)